INTERFERENCE OF INDONESIAN STUDENTS IN LEARNING ENGLISH PRONUNCIATION - Amelia, Eva; Suryani, Ahmad; Wahyudi, Muhammad Ade; Hakim, Lukman ((JELE) Journal Of English Language and Education, 2021)
Indonesian students have several difficulties while studying the English language, but one of the most challenging is determining how to correctly pronounce the different English sounds. Â It is difficult for Indonesian students to master the pronunciation of English since their native language (Indonesian language) interferes with their attempts to study English as a foreign language. According to the source of the problem, there are significant discrepancies in the pronunciation systems of the two languages, which is the root cause of the interfering noises that were heard throughout the broadcast. They may be found in various areas, including phonemes, phonetic characteristics, word stress, sentence stress, and intonation, to mention a few.